KEWENANGAN PETUGAS DINAS PERHUBUNGAN DALAM PENEGAKAN HUKUM KENDARAAN ANGKUTAN BARANG DI KOTA SAMARINDA - Nur Fauzia (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACT This study aims to determine the authority of the Department of Transportation officials in law enforcement of freight transportation vehicles in Samarinda City and to determine the obstacles faced by the Transportation office in enforcing the law of transportation of goods in Samarinda City. This research method is a type of normative legal writing. Source of legal materials are obtained from secondary legal materials, sources of primary legal materials, and non-legal materials. The type of research used is normative or doctrinal legal research which is also referred to as library research or document study because this research is carried out or aimed at written regulations or other legal materials. With the statutory research approach and the conceptual approach, the approach is carried out by examining all the laws and regulations that are relevant to the legal issues being addressed.The result of the study showed that the authority of the Transportation Service Officers in enforcing the legal transport of goods in Samarinda City was in accordance with the Traffic and Road Transportation law, with technical regulations being Government Regulations Number 80 of 2012 concerning Procedures for Inspecting Motorized Vehicles on the Road and Enforcement of Past Violations Road Traffic and Transportation. The obstacle faced by the Department of Transportation officials in enforcing the law of freight vehicles in Samarinda City is that it still often occurs in the field with a lack of understanding of the rules that apply to the performance of each agency (the Department of Transportation with the National Police). To take action even though in general it has been regulated in Government Regulation Number 80 of 2012. Keywords : Authority; Department of Transportation; Law Enforcement; Goods Transportation